POLA KOMUNIKASI GURU DALAM PROSES PEMBELAJARAN TERHADAP SISWA DISABILITAS - Deby Fellyana Azhari (Jurnal Prodi Ilmu Komunikasi, 2023)
Patterns are forms or models that have regularity, and communication is the process of sending messages from the communicator to the recipient of the message or communicant. Communication pattern is a form or pattern of relationship between two or more people in the process of sending and receiving in the right way so that the intended message can be understood. This study aims to find out how the teacher's communication patterns with deaf students in public special schools c, Prabumulih City. Teachers in special schools use communication totally in the learning process, namely oral communication or pronunciation of words and communication through sign language. In this study used a descriptive qualitative method with the theory of symbolic interaction proposed by George Herbert Mead. With the results of the study showing that teacher communication in educating students with hearing impairments in the learning process is total communication, verbal communication, and non-verbal communication which are used simultaneously. Keywords: Communication, Teachers, Disabilities